2008 International Conference on Reconfigurable Computing and FPGAs 2008
DOI: 10.1109/reconfig.2008.11
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Implementation of a Public Key Block Cipher - MQQ, for FPGA Platforms

Abstract: -We have implemented in FPGA recently published class of public key algorithms -MQQ, that are based on quasigroup string transformations. Our implementation achieves decryption throughput of 399 Mbps on an Xilinx Virtex-5 FPGA that is running on 249.4 MHz. The encryption throughput of our implementation achieves 44.27 Gbps on four Xilinx Virtex-5 chips that are running on 276.7 MHz. Compared to RSA implementation on the same FPGA platform this implementation of MQQ is 10,000 times faster in decryption, and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…This algorithm depends on multivariate polynomial changes of almost quadratic and grouped having the accompanying properties [30,31]. Highly parallelizable not at all like different calculations that are basically successive, the encryption acceleration is practically identical to different cryptosystems public key in view of multivariate quadratic, the decryption algorithm is same as of a symmetric block chipper, and post-Quantum Algorithm, As indicated by El-Hadely and Maia [32,31] investigations demonstrated that the equipment MQQ can be as quick as a run of the mill symmetric block cipher, being a few requests of extent quicker than algorithm, for example, RSA, DH and ECC.…”
Section: Multivariate Quadratic Almost Group (Mqq) -mentioning
confidence: 99%
“…This algorithm depends on multivariate polynomial changes of almost quadratic and grouped having the accompanying properties [30,31]. Highly parallelizable not at all like different calculations that are basically successive, the encryption acceleration is practically identical to different cryptosystems public key in view of multivariate quadratic, the decryption algorithm is same as of a symmetric block chipper, and post-Quantum Algorithm, As indicated by El-Hadely and Maia [32,31] investigations demonstrated that the equipment MQQ can be as quick as a run of the mill symmetric block cipher, being a few requests of extent quicker than algorithm, for example, RSA, DH and ECC.…”
Section: Multivariate Quadratic Almost Group (Mqq) -mentioning
confidence: 99%
“…Furthermore according to El-Hadely and Maia [2,34] experiments showed that the hardware MQQ can be as fast as a typical symmetric block cipher, being several orders of magnitude faster than algorithms such as RSA, DH and ECC.…”
Section: Multivariate Quadratic Quasigroup (Mqq)mentioning
confidence: 99%
“…Performance comparison of RSA, ECC and MQQ in CPU cycles. [42] According to [2] that implemented in FPGA a 160bit instance of the newly published public key scheme MQQ, the results of their implementation and the Table 4 show that in hardware, MQQ public key algorithm in encryption and decryption (that means also in verication and signing) can be as fast as a typical block cipher and is several orders of magnitude faster than most popular public key algorithms like RSA, DH or ECC. …”
Section: Groupmentioning
confidence: 99%
“…The scheme combines the advantages of both the MQ polynomials and quasigroups. On the one hand, as it only needs the basic operations of XOR and AND between bits during the encryption and decryption processes, MQQ scheme performs several orders of magnitude faster than the traditional public key algorithms like RSA, DH or ECC [13]. On the other hand, the key space of MQQ scheme is large enough against an exhaustive key-search attack [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the key space of MQQ scheme is large enough against an exhaustive key-search attack [12]. Moreover, this scheme offers flexibility in its implementation from parallelization point of view [13]. In a recent work [14], MQQ scheme has been successfully used in wireless sensor network.…”
Section: Introductionmentioning
confidence: 99%